THE EFFECT OF THE GREAT PARENTS SCHOOL (SOTH) PROGRAM ON STUNTING - Kartikawati, Anis; Purwono, Rudi (Airlangga Development Journal, 2025)
Stunting is one of the major health problems faced by developing countries, particularly Indonesia. Various programs established to decrease stunting. Sekolah Orang Tua Hebat (SOTH) is new program which targets parents/caretaker on stunting alleviation. This study aims to analyze the effect of SOTH on stunting in Lamongan Regency, Indonesia. We utilize panel data analysis in village level. We find that SOTH did not affect stunting directly. On the other hand, the multiplier effect of this program could potentially increase the understanding of child fostering. Therefore, promoting this program is necessary to complement existing stunting alleviation program in Indonesia.